Complications of pectoralis major myo‐cutaneous flap, anterolateral thigh flap and radial forearm free flap after total laryngectomy with partial pharyngectomy: A systematic review and network meta‐analysis. Issue 3 (19th October 2022) - Costantino, Andrea; Festa, Bianca Maria; Kim, Se‐Heon; Baik, Fred M.; Wang, Chen‐Chi; Pirola, Francesca; Malvezzi, Luca; Spriano, Giuseppe; Mercante, Giuseppe; De Virgilio, Armando
Abstract: Background: No consensus exists regarding the most effective reconstruction after total laryngectomy with partial pharyngectomy (TLwPP). This study aims to compare different reconstructive techniques (pectoralis major myo‐cutaneous flap, PMMCF; anterolateral thigh flap, ALTF; radial forearm free flap, RFFF) after TLwPP in terms of pharyngocutaneous fistula (PCF), stenosis and feeding tube dependence (FTD) incidence. Methods: The Scopus, PubMed/MEDLINE, Cochrane Library, and Google Scholar databases were searched. A single‐arm meta‐analysis was performed for PCF incidence, stenosis incidence, and FTD incidence on the entire cohort. An arm‐based network analysis was conducted to compare three different surgical interventions (PMMCF, ALTF, RFFF). Results: A total of 13 studies and 232 patients were included in the network meta‐analysis. The lowest PCF absolute risk was measured for the RFFF (11.7%, 95% CI: 2.8%–33.4%), compared to the ALTF (13.4%, 95% CI: 4.5%–32.1%) and the PMMC (49.0%, 95% CI: 19.2%–79.3%). The RFFF showed a stenosis absolute risk of 0.0% (95% CI: 0.0%–1.1%), while a higher stenosis incidence was measured for the ALTF (5.7%, 95% CI: 0.8%–25.2%) and the PMMCF (11.6%, 95% CI: 0.8%–55.1%). The RFFF showed the lowest absolute risk of FTD incidence (6.8%, 95% CI: 0.5%–28.1%) compared to the other reconstructive techniques (PMMCF: 12.4%, 95% CI: 2.4%–42.1%; ALTF: 17.5%, 95% CI: 6.4%–38.9%). Conclusions: The RFFF seems the best choice for reconstruction of partial pharyngeal defects after TLwPP due to the lower incidence of PCF, stenosis and FTD compared to the ALTF and the PMMCF.